3D micro-mechanical modelling of orthogonal cutting of UD-CFRP using smoothed particle hydrodynamics and finite element methods. (15th June 2019) - Abena, Alessandro; Essa, Khamis
Abstract: FE models of orthogonal cutting of FRP composites are usually used implementing element deletion when the failure condition has been reached. This typically results in loss of contact between tool and workpiece during cutting leading to very poor thrust force prediction. In this study, a comprehensive three-dimensional numerical model of orthogonal cutting of UD-CFRP employing the SPH method at the micro-scale level is developed for different fibre orientations ( θ = 0 °, 45°, 90°, 135°). Results are compared with those obtained by a FEM model and against experimental findings. Results show that the SPH method is able to improve prediction of cutting force ( ∼ 30% at θ = 0 ° ) and thrust force ( ∼ 30% at θ = 90 °, 135°), showing also a chip formation mechanism closer to that experimentally observed. In addition, the developed approach allows simulating the bouncing back, that for θ = 0 ° results equal to the cutting edge radius ( ∼ 5 μ m), as expected from the literature, and calculating the actual depth of cut.